1970
DOI: 10.1037/h0028648
|View full text |Cite
|
Sign up to set email alerts
|

Validation of employment tests for telephone company installation and repair occupations.

Abstract: Test validation data for telephone company installation and repair occupations are presented. Criteria used are proficiency measures obtained from a Learning Assessment Program (LAP), which is described. The samples consist of employees, 211 minority and 219 nonminority, of five geographically spread telephone companies. Five aptitude tests were administered at or immediately following employment. The 5s went through the LAP prior to obtaining onthe-job experience. Test scores were correlated with the proficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

1970
1970
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 2 publications
(4 reference statements)
6
17
0
Order By: Relevance
“…Thus, the absence of differential validity suggests that the tests were fair for the ethnic groups. Similar results regarding differential validity for ethnic groups have been found by Cleary (1968) in predicting scholastic performance of students, Grant and Bray (1970) in predicting job proficiency of telephone company installation and repair workers, and Tenopyr (1967) in predicting training success of airline employees. Boehm's (1972) comprehensive review of studies addressing black-white differences in validity of employment and training selection procedures also yielded similar conclusions.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the absence of differential validity suggests that the tests were fair for the ethnic groups. Similar results regarding differential validity for ethnic groups have been found by Cleary (1968) in predicting scholastic performance of students, Grant and Bray (1970) in predicting job proficiency of telephone company installation and repair workers, and Tenopyr (1967) in predicting training success of airline employees. Boehm's (1972) comprehensive review of studies addressing black-white differences in validity of employment and training selection procedures also yielded similar conclusions.…”
Section: Discussionsupporting
confidence: 70%
“…In each of these six instances, the use of the regression line based on Anglos alone would again favor, not penalize, the Negroes. Similar findings were reported by Grant and Bray (1970) from a study of telephone company installation and repair occupations. Using aptitude tests to predict success in training, they found about equal prediction for minority and nonminority trainees, but that the use of a common regression line "biases the use of the tests for making predictions somewhat in favor of minority group applicants" (p. 14).…”
Section: Validity Studiessupporting
confidence: 88%
“…Although it has been found that the slopes of both the Black and White regression lines are often similar, they frequently have different intercepts (e.g. Boehm, 1977;Field, Bayley, & Bayley, 1977;Gael, Grant, & Ritchie, 1975b;Grant & Bray, 1970;Schmidt, Berner, & Hunter, 1973). Furthermore, the intercept of the regression line for Blacks is frequently found to be lower than that for Whites, indicating that the use of a common regression line would over-predict job performance for Blacks according to the Cleary rule.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%
“…Studies used to assess differential prediction normally use a combination of ability tests, including not only cognitive ability, but also knowledge and special skills such as clerical speed and accuracy (e.g. Boehm, 1977;Field et al, 1977;Gael et al, 1975b;Grant & Bray, 1970;Schmidt et al, 1973). Therefore, these differential prediction studies cannot necessarily be generalized to characterize CATs exclusively.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%